Preoperative Peripheral Blood Count in Breast Carcinoma: Predictor of Prognosis or a Routine Test - Amrit Pal Singh Rana; Manjit Kaur; B. Zonunsanga; Arun Puri; Amarjit Singh Kuka (International Journal of Breast Cancer)
Background. Peripheral blood count is the first investigation to be done in every patient before surgery. As strong relationship exists between cancer and immune response of the body, clinical stage at presentation and altered hematological parameters can influence the progression of cancer and vice versa. Settings and Design. It is a case control study of total 50 cases (35 cases of carcinoma breast and 15 cases of benign breast disease). Methods. A case control study was carried out; 35 cases of breast cancer patients were taken prior to surgery and chemotherapy with 15 cases of benign breast disease as control. Clinical staging according to the tumor, node, and metastasis classification (TNMc) was done and was correlated with complete blood count (CBC). Results. All the cancer patients were females with overall mean age of 47.96±13.84 years. Amongst all altered blood parameters, correlation of absolute lymphocytic count (p value 0.001) with TNMc staging was found significant. Particularly, decrease in absolute leucocytic count was observed with increase in stage of breast carcinoma. Conclusions. The stage-specific mean values of absolute lymphocytic counts of preoperative breast cancer patients can be used as an economical tool to know the evolution of disease.